1964
DOI: 10.1152/jappl.1964.19.2.279
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of duration of left ventricular ejection in normal young men

Abstract: The factors governing the duration of ejection were studied by statistical techniques at rest and during exercise in man. Data consist of 207 points in 20 subjects. Linear stepwise regression analysis results in the following formula for the prediction of the duration of ejection from the heart rate, stroke index, and the aortic diastolic pressure: duration of ejection = .36646 - .00108 (rate) - .00036 (diastolic pressure) + .00076 (stroke index). The correlation coefficient is 0.90 on comparison with the meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
2

Year Published

1968
1968
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 0 publications
2
14
2
Order By: Relevance
“…If the slope of the relationship of one variable with another is not altered by an intervention such as exercise, but the position of the curve is shifted; then the regression derived from pooling all the data before and after the intervention will be different from the regressions which are obtained from treating the data separately. This appears to be the explanation for the differences in slope found in the relationship between heart rate and ejection time in previous studies (27)(28)(29)32).…”
Section: Column 5)mentioning
confidence: 57%
See 1 more Smart Citation
“…If the slope of the relationship of one variable with another is not altered by an intervention such as exercise, but the position of the curve is shifted; then the regression derived from pooling all the data before and after the intervention will be different from the regressions which are obtained from treating the data separately. This appears to be the explanation for the differences in slope found in the relationship between heart rate and ejection time in previous studies (27)(28)(29)32).…”
Section: Column 5)mentioning
confidence: 57%
“…These studies have shown that the duration of ejection varies directly with stroke volume, but that changes of stroke volume have little or no effect on the duration of total systole. Previous work in man has involved the use of drugs (23,24), exercise (25)(26)(27), or other maneuvers (28) in individual subjects, comparisons of patients with different diseases (29), or the statistical analysis of pooled single measurements from large numbers of individuals (27,28,30,31). In studies of this type the inotropic background will vary from one individual to another.…”
Section: Column 5)mentioning
confidence: 99%
“…In man, attention has been predominantly directed at the relationship between heart rate and the phases of systole both in groups and in individual subjects. Studies in single subjects have involved the use of exercise (10)(11)(12)(13)(14)(15)(16)(17), drugs (11,18,19), or other maneuvers (15,20,21), to alter heart rate. The resulting changes in the duration of both ejection and systole depend not only on heart rate, but also upon changes in stroke volume and in the inotropic background produced by the interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Although experimental work in the dog (7,8) has indicated that stroke volume was a major determinant of the duration of ejection, several authors have examined the multiple correlation of duration of ejection, stroke volume, and heart rate in man with incongruous results. From such studies it has been concluded that stroke volume is of no importance in determining duration of ejection (16), that stroke volume has a significant but relatively minor effect (13), and that stroke volume is an important determinant of duration of ejection (20). The reasons for these conflicting results apparently stem from the use of pooled data from many individuals and the use of interventions which alter both stroke volume and heart rate simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…They are based on spontaneous variation in heart rate in normal subjects, studied fasting, and between 08.00 h and 10.00 h. However, they are not unique. Jones & Foster (1964), using stepwise regression analysis, noted that the major variable affecting ejection time was heart rate, but defined additional significant relations with stroke volume and arterial pressure. The slope of their regression line differed from that of Weissler et al (1968), possibly because of their use of exercise to vary heart rate.…”
Section: Determinants Of the Systolic Time Intervalsmentioning
confidence: 99%